Navigating Ruling Relations in Institutional Ethnographic Fieldwork: Reflections on the Ontological Shift and Activists’ Work - Kuk, Hye-Su (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2024)
Based on year-long fieldwork on activist-educators’ work in South Korea, I reflect on how my research complicates the ontological shift in institutional ethnography: that is, the shift that emphasizes how ruling relations are coordinated through the very actions of people. I discuss two facets of reflective pauses. First, I discuss how the ruling relations of research practice in South Korea render the ontological shift “slippery.” I argue for a need to understand the ontological shift in relation to external contexts of research instead of an individualized approach. Second, I detail the process of a comparative research design looking at activist-educators with differing levels of engagement with the Korean state. I highlight how a transitional void that emerged after democratization prompted different activist strategies. I call for a need to reconsider the connection between activists’ work and institutional ethnography, where investigating activists’ work provides a lens into the ruling relations.